Peran Komunikasi Efektif dalam Mengembangkan Kompetensi Edupreneurship - Alisia Zahro’Atul Baroroh; Nur Kholis; Mochamad Iskarim (Pusat riset dan Inovasi Nasional, 2026)
Communication is a fundamental element in the development of entrepreneurship, particularly within edupreneurship, which integrates educational innovation with entrepreneurial values to address contemporary challenges in education. In an increasingly competitive and digitally driven educational landscape, edupreneurs are required not only to possess pedagogical competence but also strong communication skills to sustain and scale their initiatives. This study aims to analyze the role of effective communication in strengthening edupreneurship competencies. The research employs a literature review method by synthesizing and analyzing relevant theories and previous studies on communication, entrepreneurship, and edupreneurship. The findings indicate that effective communication plays a significant role in enhancing key edupreneurship competencies, including negotiation skills, leadership capacity, personal branding, and adaptability to digital transformation. Communication also functions as a strategic tool for building trust, expanding professional networks, fostering collaboration, and creating supportive learning ecosystems within educational enterprises. Moreover, effective communication enables edupreneurs to articulate value propositions clearly, manage stakeholders efficiently, and respond flexibly to dynamic changes in educational markets. The implications of this study emphasize that communication competence is not a complementary skill but a core requirement for sustainable edupreneurship development. Therefore, systematic communication training and the integration of communication-based learning strategies are strongly recommended within entrepreneurship education programs, particularly for prospective edupreneurs, to support long-term innovation, competitiveness, and sustainability in the education sector.